Preparation of Super - Hydrophobic Coating on the Surface of Mine Water Flowing and Its Scale Inhibition Mechanism - JU Zeng - xin, HU Li - na, NIGATI Yusufu (Cailiao Baohu)
In the process of desalination of mine water, due to the high hardness of the water quality, the surface of equipment and pipelines were scaled, which affected the efficiency of water production and improved the cost of water production. In this work, a superhydrophobic coating was prepared on the surface of stainless steel 316 substrate by spraying method, and a comparative experimental study of CaCO3 scaling was carried out. The composition of foulant on the sample surface was analyzed by scanning electron microscope (SEM) and X - ray diffraction (XRD). Result showed that the morphology of CaCO3 on the surface of the non - superhydrophobic coating was a small amount of rhombohedral crystals and typical calcite. The morphology of CaCO3 on the surface of the 316 stainless steel with superhydrophobic coating was needle - like and flower - like aragonite with soft texture, and the nucleation theory was used for the first time to analyze the scale inhibition mechanism of the superhydrophobic coating and determine the nucleation function of the superhydrophobic coating. Meantime, the effects of temperature and flow rate on the scaling performance of CaCO3 were studied, and the dynamic and static comparison experiments were carried out. It was found that when the flow rate was constant, the higher the temperature, the greater the CaCO3 fouling rate; when the temperature was constant, the greater the flow rate, the lower the CaCO3 fouling rate. This method showed a good application prospect in the scale inhibition and self - cleaning of the mine water flowing surface.